Impact of an Opioid Safety Initiative on Patients Undergoing Total Knee Arthroplasty: A Time Series Analysis. (August 2019) - Chen, Qi; Hsia, Hung-Lun; Overman, Robert; Bryan, William; Pepin, Marc; Mariano, Edward R.; Mudumbai, Seshadri C.; Buchheit, Thomas; Krishnamoorthy, Vijay; Good, Chester B.; Brookhart, M. Alan; Raghunathan, Karthik
Editor's Perspective: What We Already Know about This Topic: Opioid overuse remains rampant even in hospitals, but whether administrative opioid safety initiatives reduce use remains unclear What This Article Tells Us That Is New: The authors evaluated the effects of a Veterans Administration national Opioid Safety Initiative using interrupted time series analysis to compare trends before and after starting the initiative There was a trivial increase in pain scores, and a substantial reduction in patients with chronic preoperative and postoperative opioid prescriptions Background: The Opioid Safety Initiative decreased high-dose prescriptions across the Veterans Health Administration. This study sought to examine the impact of this intervention ( i.e., the Opioid Safety Initiative) on pain scores and opioid prescriptions in patients undergoing total knee arthroplasty. Methods: This was an ecological study of group-level data among 700 to 850 patients per month over 72 consecutive months (January 2010 to December 2015). The authors examined characteristics of cohorts treated before versus after rollout of the Opioid Safety Initiative (October 2013). Each month, the authors aggregated at the group-level the differences between mean postoperative and preoperative pain scores for each patient (averaged over 6-month periods), and measured proportions of patients (per 1, 000) with opioid (and nonopioid) prescriptions for more than 3 months in 6-month periods, preoperatively and postoperatively. The authors compared postintervention trends versus trends forecasted based on preintervention measures. Results: After the Opioid Safety Initiative, patients were slightly older and sicker, but had lower mortality rates (postintervention n = 28, 509 vs. preintervention n = 31, 547). Postoperative pain scores were slightly higher and the decrease in opioid use was statistically significant, i.e., 871 (95% CI, 474 to 1, 268) fewer patients with chronic postoperative prescriptions. In time series analyses, mean postoperative minus preoperative pain scores had increased from 0.65 to 0.81, by 0.16 points (95% CI, 0.05 to 0.27). Proportions of patients with chronic postoperative and chronic preoperative opioid prescriptions had declined by 20% (n = 3, 355 vs. expected n = 4, 226) and by 13% (n = 5, 861 vs. expected n = 6, 724), respectively. Nonopioid analgesia had increased. Sensitivity analyses confirmed all findings. Conclusions: A system-wide initiative combining guideline dissemination with audit and feedback was effective in significantly decreasing opioid prescriptions in populations undergoing total knee arthroplasty, while minimally impacting pain scores. Abstract : The authors evaluated the effects of a Veterans Administration national Opioid Safety Initiative using interrupted time series analysis to compare trends before and after starting the initiative. There was a trivial increase in pain scores, and a substantial reduction in patients with chronic preoperative and postoperative opioid prescriptions.Supplemental Digital Content is available in the text.